Cytological Characteristics of Pleural Effusion with Variations in 96% Alcohol Fixation Time Using Papanicolaou Staining - Priska Alicia Vansugisti; Ary Nurmalasari; Euis Tia Istianah; Rahayu Nirmatul Mutmainah (Laboratory Journal of Infectious Diseases, 2026)
Pleural effusion is a clinical condition that may indicate serious underlying diseases, including infection, malignancy, and systemic disorders. Cytological examination of pleural fluid plays an important role in determining the possible etiology of pleural effusion and requires proper fixation to preserve cellular morphology and staining quality. This study aimed to evaluate the cytological characteristics and preparation quality of pleural fluid specimens fixed in 96% alcohol for 15 minutes and 30 minutes using the Papanicolaou staining method. This quasi-experimental study included 16 pleural fluid samples obtained from routine laboratory examinations. Each sample was processed into four cytological smears, consisting of two duplicate smears fixed in 96% alcohol for 15 minutes and two duplicate smears fixed in 96% alcohol for 30 minutes. A total of 64 smears were evaluated, with 32 smears in each fixation group. All smears were stained using the Papanicolaou method and assessed microscopically based on background appearance, cellular morphology, nuclear characteristics, and overall staining quality. Of the 32 smears fixed for 15 minutes, 20 smears (62,5%) were classified as poor quality and 12 smears (37,5%) as good quality. In contrast, among the 32 smears fixed for 30 minutes, 3 smears (9,4%) were classified as poor quality and 29 smears (90,6%) as good quality. These findings indicate that fixation using 96% alcohol for 30 minutes produces better cytological preparation quality than fixation for 15 minutes. Therefore, a 30-minute fixation period is recommended to support optimal cytological evaluation and diagnostic accuracy.